The Cognitive Effects of Micronutrient Deficiency: Evidence from Salt Iodization in the United States. Issue 2 (8th April 2017) - Feyrer, James; Politi, Dimitra; Weil, David N.
Abstract: Iodine deficiency is the leading cause of preventable mental retardation in the world today. The condition, which was common in the developed world until the introduction of iodized salt in the 1920s, is connected to low iodine levels in the soil and water. We examine the impact of salt iodization on cognitive outcomes in the United States by taking advantage of this natural geographic variation. Salt was iodized over a short period of time beginning in 1924. We use military data collected during World War I and World War II to compare outcomes of cohorts born before and after iodization in localities that were naturally poor and rich in iodine. We find that for the one-quarter of the population most deficient in iodine this intervention raised intelligence quotient (IQ) by approximately one standard deviation. Our results can explain roughly one decade's worth of the upward trend in IQ in the United States (the Flynn effect). We also document a large increase in thyroid-related deaths following the countrywide adoption of iodized salt, which affected mostly older individuals in localities with high prevalence of iodine deficiency. (JEL: I12, I18, J24, N32)